Effect of Foliar Application of Boron, Auxin, and Methionine and Their Interactions on Some Quality Attributes of ’Shada Al-Aswad’ Grape (Vitis Vinifera L.) Fruits - Lateef, Sabreen Mohammed (American Journal of Botany and Bioengineering, 2026)
This experiment was carried out in a private vineyard in Al-Dujail District, Salah al-Din Governorate, Iraq for the growing season of 2024 to study the influence of foliar application boron, auxin and methionine on some qualitive properties of ’Shada Al-Aswad’ grapevine (Vitis vinifera L.) fruits. The experiment was conducted in a randomized complete block design (RCBD) with 3 replications and included two boron levels (0 and 10 g L-¹), three auxin concentrations [0, 0.015 and 0.030 mg L-1] and three methionine concentrations [0, 0.010 or 0.030 g L-1]. Results indicated that foliar boron significantly improved some fruit quality attributes by elevated the concentration of sugar, anthocyanin and carbohydrate contents of 7.04%0-1 (793.15 mg 100 g⁻¹), 283.68 mg 100 g⁻¹; 13.71%, at mean levels with early spring among two treatments with decreasing in acidity and nitrate content recorded to be %0-1;and mmg/ mi01g⁻¹,.respectively. This emphasizes the importance of boron in controlling physiological processes associated with fruit quality. Moreover, the elicited metabolite content by auxin at 0.030 mg L⁻¹were significantly higher in TSS (14.47%), sugars (6.77%) anthocyanins(TSAC) (271.48 mg/100 g),CHO(13.48%) and much lower in acidity than nitratesabout or equal to 6 h (0.60% and 0,87mg/100g). This is indicative of its regulatory role on fruit ripening and synthesis of quality-related compounds. Additionally, foliar methionine application (0.030 g L⁻¹) was able to enhance fruit quality by increasing anthocyanin pigment and carbohydrate contents and decreasing acidity percentages at 271.42 mg 100 g⁻¹, 13.48%, and 0.60% respectively. This is a proof of its contribution to biochemical pathways leading to better quality of crop. In general, the results indicate that the application of these compounds especially at the highest applied concentrations can successfully improve quality characteristics of ’Shada Al-Asward’ grapes. It is advisable to include them in the current nutrition programs of vineyards placed under similar environmental conditions.